2021
DOI: 10.1002/clt2.12038
|View full text |Cite
|
Sign up to set email alerts
|

Anaphylactic risk related to omalizumab, benralizumab, reslizumab, mepolizumab, and dupilumab

Abstract: Background Monoclonal antibodies (mAbs) are novel, effective therapeutics for the treatment of inadequately controlled severe asthma. Knowledge of the anaphylaxis risks related to different mAbs is essential for their appropriate and safe administration. This study aimed to evaluate the associations between different mAbs and anaphylactic reactions by applying statistical approaches to pharmacovigilance data. Methods This was a retrospective study using data from the US Food and Drug Administration Adverse Eve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(45 citation statements)
references
References 25 publications
(34 reference statements)
8
37
0
Order By: Relevance
“…Other studies also showed that the fatal reactions to AIT were low (Epstein et al, 2021). Death rate of omalizumab associated anaphylaxis was a little lower than that of dupilumab associated anaphylaxis, which was consistent with another real-world study about anaphylaxis related to biologis (Li et al, 2021). In a systematic review for the EAACI guidelines of recommendations on the use of biologics in severe asthma, omalizumab might increase serious adverse events in adolescent/adults (Risk ratio 1.62, 95%CI 0.76-3.45) with low certainty of evidence.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…Other studies also showed that the fatal reactions to AIT were low (Epstein et al, 2021). Death rate of omalizumab associated anaphylaxis was a little lower than that of dupilumab associated anaphylaxis, which was consistent with another real-world study about anaphylaxis related to biologis (Li et al, 2021). In a systematic review for the EAACI guidelines of recommendations on the use of biologics in severe asthma, omalizumab might increase serious adverse events in adolescent/adults (Risk ratio 1.62, 95%CI 0.76-3.45) with low certainty of evidence.…”
Section: Discussionsupporting
confidence: 83%
“…The anaphylactic symptoms of omalizumab and dupilumab were more common in female than in male. In another study of biologics related anaphylaxis based on FAERS, females made up a large part of reported cases (Li et al, 2021). A report of anaphylaxis associated with omalizumab also revealed a preponderance of female subjects (84%) (Lieberman et al, 2017).…”
Section: Discussionmentioning
confidence: 99%
“…Men had significantly lower risk for iDAR in all treatment groups, and older adults were at higher risk for iDAR in all treatment groups. In a study using FAERS to evaluate anaphylactic risk related to dupilumab use for AD and asthma, men were less likely to experience anaphylaxis, as was the trend observed across the other four monoclonal antibodies studied 33 . Real‐world data for CRSwNP‐tx using dupilumab is lacking 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This response may be mild, transient, subclinical, or it may be a serious and potentially fatal reaction when the immune system overreacts (hypersensitivity). 9,10 In addition, mAbs treatment is used primarily for patients with severe asthma. 11 No single cytokine is responsible for the entire pathogenesis of asthma.…”
Section: Introductionmentioning
confidence: 99%